Diet formulation using distiller dried grain solubles with different levels on performance of laying chicken growers - Sudarisman, Sudarisman; Yunianta, Yunianta; Suryayuliana, Ifan Dwi (Politeknik Negeri Jember, 2025)
This study aims to determine the performance of laying hens in the grower phase that are given formulated feed treatment using distiller dried grain solubles (DDGS) at different levels. The research materials are 72 New Lohman Brown strain DOC chickens, and basal feed. The experimental design used a completely randomized design with a one-way pattern with 4 treatments and 3 replications, each treatment group consisting of 6 chickens. Feed treatments consisted of (T1) 0% DDGS formula feed (T2) 10% DDGS formula feed, (T3) 20% DDGS formula feed and (T4) 30% DDGS formula feed. The research variables were feed consumption, body weight gain and feed conversion ratio of laying hens. Data analysis using analysis of variance (ANOVA) to determine the level of significance at the standard of 0.05. then continued with Duncan multiple range test (DMRT) analysis. The results of the study showed that the provision of DDGS at various levels did not affect the performance of laying hens in the grower phase. The conclusion of the study is that the provision of destillers dried grains soluble up to a level of 30% in the basal feed formulation is able to maintain feed consumption, body weight gain and feed conversion ratio of laying hens in the grower phase.